Zeus : king of the gods, god of sky and storms - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek god Zeus, the king of the gods and the god of sky and storms.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
6.5
3-6.
3-6
Keywords: Mythology, Greek -- Juvenile literature; Zeus (Greek deity) -- Juvenile literature; Mythology, Greek; Zeus (Greek deity); Greek mythology; Zeus (Greek deity)